2016
DOI: 10.1158/0008-5472.can-15-3486
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Marginal Zone Granulocytes Acquire an Accentuated Neutrophil B-Cell Helper Phenotype in Chronic Lymphocytic Leukemia

Abstract: Recruitment of tumor-associated macrophages and neutrophils (TAM and TAN) to solid tumors contributes to immunosuppression in the tumor microenvironment; however, their contributions to lymphoid neoplasms are less clear. In human chronic lymphocytic leukemia (CLL), tumor B cells lodge in lymph nodes where interactions with the microenvironment occur. Tumor cell homing stimulates proliferation, such that engagement of the B-cell receptor is important for malignant progression. In the Em-Tcl1 murine model of CLL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…Although we did not observe a BAFF or APRIL differential expression between circulating neutrophils from HD and CLL patients, it is conceivable that, once in the lymphoid tissues, reprogrammed CD16 high CD62L dim cells receive additional signals from the microenvironment to promote leukemic B cell survival. This hypothesis is supported by a previous report in the Eμ‐TCL1 murine model of CLL that exhibited an expanded neutrophil population with B‐helper properties in the spleen of leukemic mice which does not exist in the bone marrow, suggesting that the local environment is critical for shaping the gene expression program of B helper neutrophils.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Although we did not observe a BAFF or APRIL differential expression between circulating neutrophils from HD and CLL patients, it is conceivable that, once in the lymphoid tissues, reprogrammed CD16 high CD62L dim cells receive additional signals from the microenvironment to promote leukemic B cell survival. This hypothesis is supported by a previous report in the Eμ‐TCL1 murine model of CLL that exhibited an expanded neutrophil population with B‐helper properties in the spleen of leukemic mice which does not exist in the bone marrow, suggesting that the local environment is critical for shaping the gene expression program of B helper neutrophils.…”
Section: Resultssupporting
confidence: 82%
“…e). Given that longer lifespan of TANs has been associated with increased expression of Bfl‐1, an antiapoptotic member of the Bcl‐2 family, we evaluated Bfl‐1 expression on HD‐neutrophils exposed to CM. By Western blot, we found that Bfl‐1 levels were significantly upregulated in HD‐neutrophils incubated for 18 hr in CM compared to those incubated in control medium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…with 1 mg/kg body weight FTY720 (Cayman Chemical), a S1P 1 , S1P 3 , S1P 4 , and S1P 5 agonist. Three hours later mice were killed and peripheral blood and spleens were further analyzed by flow cytometry and immunohistology.…”
Section: Chemotaxis Assaymentioning
confidence: 99%
“…2 In CLL, tumor cells interact with a variety of different stromal cells, such as mesenchymal stromal cells, monocytederived nurse-like cells, and also with T lymphocytes and myeloid cells. 3,4 Employing the murine Em-Tcl1 transgenic model of CLL, we recently demonstrated that malignant B cells home to the B cell follicle, where they find a growth-promoting microenvironment in close proximity to the follicular dendritic cell network (FDC). FDCs secrete CXCL13, the ligand for the chemokine receptor CXCR5, and the CXCL13/CXCR5 signaling axis mediates the recruitment of leukemic cells toward follicular FDCs.…”
Section: Introductionmentioning
confidence: 99%